2012
DOI: 10.2133/dmpk.dmpk-11-rg-135
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of N-Glycosylation on the Glucuronidation of Zidovudine and Morphine by UGT2B7 Expressed in HEK293 Cells

Abstract: UDP-glucuronosyltransferases (UGTs) are glycoproteins in endoplasmic reticulum membranes. UGT2B7 is an important UGT isoenzyme expressed in human liver and glucuronidates various endogenous and exogenous substances. Although this enzyme has three potential N-glycosylation sites (asparagine at positions 67, 68 and 315), no information is available on the actual glycosylated sites and the effects of N-glycosylation on its enzymatic functions. We thus constructed HEK293 cells expressing wild-type UGT2B7 and five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…We also report the presence of i1, i2, and i4 in the Golgi, a feature that is compatible with scarce reports of weak UGT activity in this organelle (von Bahr et al, 1972;Bossuyt and Blanckaert, 2001). However, it is also plausible that these three proteins undergo chemical modifications in the Golgi; indeed, UGT2B7 is glycosylated (Nagaoka et al, 2012), a chemical modification mainly initiated and/or terminated in the Golgi (Stanley, 2011). Western blotting of centrifugation fractions and comparison of UGT2B7 signals with subcellular compartment-specific markers further substantiate that i1, i2, and i4 are all residents of the ER and Golgi, whereas i2 and i4 can also be found in the cytoplasm, in which they may have roles distinct from that of i1 inhibition.…”
Section: Discussionsupporting
confidence: 91%
“…We also report the presence of i1, i2, and i4 in the Golgi, a feature that is compatible with scarce reports of weak UGT activity in this organelle (von Bahr et al, 1972;Bossuyt and Blanckaert, 2001). However, it is also plausible that these three proteins undergo chemical modifications in the Golgi; indeed, UGT2B7 is glycosylated (Nagaoka et al, 2012), a chemical modification mainly initiated and/or terminated in the Golgi (Stanley, 2011). Western blotting of centrifugation fractions and comparison of UGT2B7 signals with subcellular compartment-specific markers further substantiate that i1, i2, and i4 are all residents of the ER and Golgi, whereas i2 and i4 can also be found in the cytoplasm, in which they may have roles distinct from that of i1 inhibition.…”
Section: Discussionsupporting
confidence: 91%
“…Many drugs, such as metoclopramide, chloramphenicol, p-aminobenzoic acid, and zidovudine, can be metabolized into their respective glucuronides [13][14][15][16] . Fortunately, morphine-6-glucuronied possesses similar pharmacological activity as morphine and has been successfully developed as a frontline analgesic drug.…”
Section: Acta Pharmacologica Sinicamentioning
confidence: 99%
“…The nearly identical results and conclusions of the two studies indicate that the similarity between active recombinant UGTs that were expressed in HEK293 cells and His-tagged UGTs from baculovirus-infected insect cells is very high. It may be added here that in contrast to the results we (unpublished data) and Nakajima et al (2010) got with UGT1A9, a very recent study found that N-glycosylation affects the activity of UGT2B7 that was expressed in HEK293 cells (Nagaoka et al, 2012). The reason for this difference is currently unclear.…”
Section: Zhang Et Almentioning
confidence: 56%